Handbook of logic in computer science. Volume 5, Logic and algebraic methods - Abramsky, Samson, 1953-; Gabbay, Dov M., 1945-; Maibaum, Thomas S. E., 1947- (Oxford : Clarendon Press ; New York : Oxford University Press, 2000)
This handbook volume covers fundamental topics of semantics in logic and computation. The chapters (some monographic in length), were written following years of co-ordination and follow a thematic point of view. The volume brings the reader up to front line research, and is indispensable to any serious worker in the areas.
V. 1. Background, mathematical structure -- v. 2. Background, computational structure -- v. 3. Semantic structures -- v. 4. Semantic modelling -- v. 5. Logic and algebraic methods.
Includes bibliographical references and indexes.
eBooks on EBSCOhost
Keywords: Computer science; Logic, Symbolic and mathematical; Electronic Data Processing; Informatique; Logique symbolique et mathématique.; COMPUTERS -- Reference; COMPUTERS -- Machine Theory; COMPUTERS -- Computer Literacy; COMPUTERS -- Information Technology; COMPUTERS -- Data Processing; COMPUTERS -- Computer Science; COMPUTERS -- Hardware -- General; Computer science; Logic, Symbolic and mathematical; Ciencia da computacao ou informatica; Logica e semantica de programacao; Programming